Conspicuous Consumption and Sophisticated Thinking - Amaldoss, Wilfred; Jain, Sanjay (Management Science, 2005)
Consumers purchase conspicuous goods to satisfy not only material needs but also social needs such as prestige. In an attempt to meet these social needs, producers of conspicuous goods like cars, perfumes, and watches, highlight the exclusivity of their products. In this paper, we propose a monopoly model of conspicuous consumption using the rational expectations framework, and then examine how purchase decisions are affected by the desire for exclusivity and conformity. We show that snobs can have an upward-sloping demand curve but only in the presence of consumers who are (weakly) followers. Laboratory tests lend support for this model prediction and for the rational expectations framework. The experimental results suggest that subjects used some degree of sophisticated thinking to arrive at their first-period decisions. Their behavior in the subsequent trials, however, can be adequately captured by a purely adaptive learning mechanism. We discuss the implications of consumer learning for optimal dynamic pricing policy by a monopolist.